Do Fulvic, Humic, and Humin Carbon Fractions Represent Meaningful Biological, Physical, and Chemical Carbon Pools?. Issue 6 (1st November 2019) - Sherrod, Lucretia A.; Vigil, Merle F.; Stewart, Catherine E.
Abstract : Humic fractions have been used to characterize soil organic matter chemistry and to identify different carbon (C) pools. The relevance of alkaline fractionation is questioned because of probable artifacts created by the extraction. Fractionation using water‐soluble organic C (WSOC), soil microbial biomass C (SMBC), permanganate‐oxidizable C (POX‐C), and particulate organic matter C (POM‐C) methodologies are sensitive to C changes. Mineral‐associated organic C (MAOC) includes WSOC and other C fractions that are not all passive C. We measured 15 proficiency soils ranging in texture, mineralogy, pH, and soil organic C (SOC) to isolate C pools with differing turnover times. We define WSOC, SMBC, POX‐C, and fulvic acid (FA) as fast pools. Slow cycling pools include POM‐C and humic acid (HA) fractions, whereas passive pools include MAOC minus WSOC (PMAOC) and humin C (HC). Data showed FA was correlated with POX‐C ( r = 0.84) as a fast C pool but was slightly more correlated with PMAOC ( r = 0.86), a passive pool. Slow C pools of HA and POM‐C were not strongly correlated ( r = 0.49). All alkaline fractions of C showed highest correlations to PMAOC, followed by POX‐C, and all showed poor correlations with POM‐C. The conventional first extraction fraction (A) yielded 70% recovery of the total FA extracted, whereas only 45% of HA was obtain. Acid soils on average had higher total FA. The regression model using physical fractionation was the best (SOC = WSOC + POM‐C + PMAOC, R 2 0.98). Only the HA fraction was a significant parameter in the regression of SOC = FA + HA + HC ( p = 0.0029). Core Ideas: Humic acid C showed the strongest correlation to all C pools except POM‐C. Recovery of fulvic C in conventional fraction was 70% of a total of three fractions. Recovery of humic acid C in conventional fraction was 45% of a total of three fractions. The distribution of fulvic (FA) to humic acid (HA) C changed with acid soils having higher FA. Regression of soil organic C = FA + HA + humin only showed the HA to be significant.